SARS-CoV-2 droplet deposition path and its effects on the human upper airway in the oral inhalation. (March 2021) - Mortazavi, Hamed; Beni, Hamidreza Mortazavy; Aghaei, Fatemeh; Sajadian, Seyed Hossein
Highlights: Computational fluid dynamics (CFD) Fluid-Structure Interaction (FSI) Discrete Phase Model (DPM) SARS-CoV-2 micro-droplet Human upper airway Abstract: Background and Objective: It is crucial to study the uptake of viral droplets in the human respiratory system to control, prevent, and treat diseases. Methods: In this study, a well-verified real anatomical model was used; the passage of air in the human upper respiratory system computed using high-quality Computer Tomography (CT) images. Then, the airflow field, along with the coronavirus micro-droplets injection, was examined in this realistic model using the Fluid-Structure Interaction (FSI) method. The Discrete Phase Model (DPM) was used to solve the field, and with the help of it, the accurate assessment of the temporal and spatial motion of the deposition in the virus-impregnated droplets was obtained in vitro in the upper respiratory system. Results: The results show that the amount of deposited micro-droplets in the nasal cavity area is meager at the inhalation only through the oral. However, it has the most residence time in this area. The most and least droplet absorption occurred in the oral cavity and larynx-trachea, respectively. Deposition efficiency is about 100% in 30 L/min flow rate and 10 μm diameter; in other words, no droplet enters the lungs. This study's other achievements include the relatively inverse relationship between droplets deposition efficiency in some parts of the upper airway, which have the most deformation in the tract. Conclusions: Utilization of a realistic model with accurate and precise computational analysis can end speculation about the deposition zone, accumulation, and the effects of the COVID-19 virus on the upper respiratory tract. On the other hand, recognizing the virus-containing droplet location can ease understanding the areas where the virus can first infect in the upper respiratory tract.